1996
DOI: 10.1210/endo.137.11.8895332
|View full text |Cite
|
Sign up to set email alerts
|

Stable and diffusible pools of nucleotides in pancreatic islet cells.

Abstract: Adenine nucleotides are thought to serve as second messengers in the control of beta-cell function by glucose, e.g. by regulating the activity of ATP-dependent K+ channels. However, their localization in different intracellular pools may mask the biologically relevant changes and complicate the interpretation of measurements in whole cells. The plasma membrane of mouse islet cells was selectively permeabilized by the alpha-toxin from Staphylococcus aureus to allow diffusion of cytoplasmic nucleotides. After pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
62
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 45 publications
3
62
0
Order By: Relevance
“…Under conditions of resting membrane potential, that easily showed the presence of such channels in N2A cells, we obtained no functional evidence for "hemichannels" in either MIN6 cells or primary pancreatic β-cells. This negative observation was made in spite of a sizable release of ATP during stimulation, which our data demonstrate to essentially occur via an exocytotic route, as anticipated by the presence of the nucleotide within the insulin-containing secretory granules (Detimary et al 1996).…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…Under conditions of resting membrane potential, that easily showed the presence of such channels in N2A cells, we obtained no functional evidence for "hemichannels" in either MIN6 cells or primary pancreatic β-cells. This negative observation was made in spite of a sizable release of ATP during stimulation, which our data demonstrate to essentially occur via an exocytotic route, as anticipated by the presence of the nucleotide within the insulin-containing secretory granules (Detimary et al 1996).…”
Section: Discussionsupporting
confidence: 43%
“…To evaluate whether MIN6 cells express "hemichannels" that could have escaped detection by the tracer uptake protocol, we tested their release of ATP under conditions favoring or preventing insulin release, since insulin secretory granules contain abundant ATP (Detimary et al 1996). Stimulation of WT MIN6 cells by 20 mM glucose elicited a sizable release of ATP (Fig.…”
Section: Min6 Cells Release Atp Only Via the Exocytotic Routementioning
confidence: 99%
“…Another source of ATP and nucleotides are insulincontaining granules of β cells [51][52][53][54]. Obermuller et al [55] showed that adenine nucleotides are released with a very short delay after stimulation, while peptides (insulin) are released later.…”
Section: Source Of Atpmentioning
confidence: 99%
“…The effluent was collected (2-min fractions) for measurement of insulin by radioimmunoassay using human insulin as standard (19). At the end, the islets were collected for determination of insulin content (18).…”
mentioning
confidence: 99%
“…The supernatant (450 l) was submitted to a triple diethylether extraction, diluted with 450 l of a buffer containing 20 mmol/l HEPES, 3 mmol/l MgCl 2 , and KOH to adjust pH at 7.75, and stored at Ϫ80°C. ATP was measured by a luminometric method, as previously described (18). Blanks and ATP standard curves in Krebs buffer were run through the entire procedure.…”
mentioning
confidence: 99%